KRITIK DAWKINS TERHADAP LIMA JALAN PEMBUKTIAN EKSISTENSI ALLAH THOMAS AQUINAS - Simplesius Sandur (STIKAS Santo Yohanes Salib Kalimantan Barat, 2020)
Thomas Aquinas (1225/1224-1274) is one of greatest thinker in the history of Medieval philosophy. He wrote his par excellence work, called Summa Theologiae. It is a theological work but rich with philosophical arguments. He established his arguments by citing Greek thinkers such as Plato and Aristotle. One of Thomas’ important argument is the prove of God’s existence or what nowdays calls as The Five Ways. Thomas presents his readers that God exists and proves it philosophically than theologically. Richard Dawkins (1941 - ) revives The Five Ways to modern readers by critizing Thomas’ arguments in his The God Delusion. Dawkins bases his critique on the evident character of modern science. His critique is supported by his Darwinism background and his efforts to promote atheism. According to Dawkins, The Five Ways does not prove anything about God. This article tries to examine and interprateThomas’ arguments on The Five Way and how Dawkins reads and critizes it from atheism point of view.